The Impact of Maximum Markup Regulation on Prices1. (30th October 2018) - Genakos, Christos; Koutroumpis, Pantelis; Pagliero, Mario
Abstract : Markup regulation is a common, yet understudied type of regulation. We analyze the repeal of maximum wholesale and retail markup regulation in an oligopolistic and vertically nonintegrated market. By comparing the prices of products affected by regulation before and after the policy change and using unregulated products as a control group, we find that abolishing regulation led to a significant decrease in both retail and wholesale prices. Our analysis provides indirect but consistent evidence that markup ceilings provided a focal point for collusion among wholesalers.